PERAN MODAL SOSIAL DALAM PENGEMBANGAN PERTANIAN ORGANIK (Studi Kasus Petani Padi Di Desa Biangloe Kecamatan Pajukukang Kabupaten Bantaeng) - Fadliadi Fadliadi; Ardi Rumallang; Ratnawati Tahir (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to determine the role of social capital in the development of organic farming. Type of research that is qualitative. The technique of determining informants was by purposive sampling, the number of informants was 7 people consisting of: Head of Biangloe Village, Chairman of the Butta Toa Natural Farmers Union, and 5 organic rice farmers. Data collection by way of observation, interviews and documentation. Data analysis through data reduction, data presentation, conclusion and verification. The research results show that the development of organic agriculture is supported by the role of elements of social capital as an adhesive value that contributes to strengthening the collective role, as follows: (1) Trust is shown through a system of openness, honesty in providing information and assistance, both moral and material (2) Social Norms in the form of unwritten rules that are inseparable from local culture and religious values (3) The social network that is owned by the presence of the Butta Toa Natural Farmers Union as a farmer learning partner, cooperatives that assist farmers in determining clearer market targets. Collaboration shown by organic and non-organic farmers through interaction and mutual assistance in working on the land.